Foucault's Orient : the conundrum of cultural difference, from Tunisia to Japan - Lazreg, Marnia (Berghahn Books, 2017)
Foucault lived for two years in Tunisia and travelled to Japan and Iran more than once. Yet throughout his critical scholarship, he insisted that the cultures of the Orient and the Occident constitute the "limit" of Western rationality. Using interviews with scholars familiar with him from Tunisia and Japan, the book examines the manner in which Foucault experienced and explained his encounters with non-Western cultures